The impact of learning motivation on academic performance among low-income college students: the mediating roles of learning strategies and mental health - Huang, Yongrong; Li, Yu; Chen, Guanglei (Frontiers in Psychology, 2025)
Financial hardship can hinder university achievement, yet the mechanisms linking motivation to performance among low-income undergraduates remain underexplored. This two-wave study tracked 316 students from three public universities in eastern China over a six-month period. Measures included intrinsic, extrinsic, and amotivation, learning strategies, perceived stress, and grade point average (GPA). Structural equation modeling revealed that the proposed model explained over 64% of the variance in GPA. Intrinsic motivation was positively associated with GPA both directly and indirectly through greater use of effective learning strategies and lower perceived stress. Extrinsic motivation contributed indirectly via strategy use, whereas amotivation showed the strongest negative relationship with GPA, operating through both reduced strategy use and elevated stress. These findings suggest that the quality of motivation shapes academic performance through self-regulated learning and stress appraisal. Interventions that foster intrinsic motivation, strengthen metacognitive and analytical strategies, and reduce stress may help narrow achievement gaps for economically disadvantaged students.